The relationships between personal factor, Health Belief Model, pesticide poisoning prevent behaviors from pesticide toxicity - สมบูรณ์, ศิริพร; รวิวรกุล, ทัศนีย์; วิทยพันธ, ยุวดี; ภุมมารักษ์, ศิปภา (Journal of Medicine and Health Sciences, 2018)
This research was a cross-sectional descriptive study applied Health Belief Model for framework design. The study aimed to determine factors associated to pesticide poisoning prevention behaviors including personal factor and perceptions of pesticide poisoning among 300 gardeners at Ongkharak district, Nakhon Nayok province using a questionnaire on the perceptions of pesticide poisoning, pesticide poisoning prevention behaviors. Data analysis was done using descriptive statistics and Pearson’s Product Moment Correlation Coefficient. Results showed that most of gardeners were female (59%), aged 22 - 59 years (78.70%), who is the owner (87.70%) of the garden, and graduate from primary school (51.30%) time of pesticide use was 10 - 20 years (54.00%), and the frequency of pesticides use was > 5 times/month (7.70%). The duration of each pesticides spraying was 1 - 3 hours (61.70%), and they had sign of acute health effect after spraying pesticides (27.30%). In addition, it was found that gardeners had pesticide poisoning prevention behaviors in middle level 1.86 (SD=0.41). The perceive risk, perceive benefit and perceive baerier had positive relations to with pesticide poisoning prevention behaviors with a statistical level p<0.01. The research suggests that pesticide poisoning prevention behaviors can be enhanced by developing program with applying Heath Belief Model to reduce health effect of pesticide toxicity among gardeners.